2008
DOI: 10.1002/tea.20243
|View full text |Cite
|
Sign up to set email alerts
|

Turkish grade 10 students' and science teachers' conceptions of nature of science: A national study

Abstract: This study aimed to assess grade 10 Turkish students' and science teachers' conceptions of nature of science (NOS) and whether these conceptions were related to selected variables. These variables included participants' gender, geographical region, and the socioeconomic status (SES) of their city and region; teacher disciplinary background, years of teaching experience, graduate degree, and type of teacher training program; and student household SES and parents' educational level. A stratified sampling approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
2
24

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 70 publications
11
90
2
24
Order By: Relevance
“…their fallibility due to their "human made" nature. Our findings in relation to conceptions about scientific modelling differ from those obtained by Dogan and Abd-El-Khalick (2008). In their study, most science teachers believed that scientific models are copies of reality rather than human inventions because scientists say they are true or because a lot of scientific observations and/or research has shown them to be true.…”
Section: Qualitative Studycontrasting
confidence: 94%
“…their fallibility due to their "human made" nature. Our findings in relation to conceptions about scientific modelling differ from those obtained by Dogan and Abd-El-Khalick (2008). In their study, most science teachers believed that scientific models are copies of reality rather than human inventions because scientists say they are true or because a lot of scientific observations and/or research has shown them to be true.…”
Section: Qualitative Studycontrasting
confidence: 94%
“…This aligns with the work of academics in the field that have found preservice and in-service teachers both hold naive views of NOS (e.g. ; Akerson, et al, 2006;Dogan & Abd-El-Khalick, 2008;Pomeroy, 1993). It is surprising that the level of NOS conceptions was indistinguishable between science and mathematics teachers on both the pre and post assessments.…”
Section: Discussionsupporting
confidence: 77%
“…It is imperative that teachers have an accurate view of NOS in order to include NOS in the science classroom and to lay the foundation for future learning and understanding of the disciplines of science, technology, engineering, and mathematics (STEM). Although teachers need developed conceptions of NOS, studies have consistently found that preservice and practicing teachers possess naive and incoherent understandings of NOS (Akerson, Morrison, & McDuffie, 2006;Dogan & Abd-El-Khalick, 2008;Firestone, Wong, Luft & Fay, 2012). This is exacerbated by the fact that science teaching practices and materials often do not specifically address NOS, and tend to emphasize science content over the processes and development of scientific knowledge ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current findings are partly supported by previous findings given above. However the studies carried out by Conley, Pintrich, Vekiri and Harrison (2004), Doğan and Abd-El-Khalick (2008), Küçük andKüçük (2011), Yalvaç, Öztürk andSarıkaya (2010), Yankayış, Güven and Türkoğuz (2014), Saydam (2010) andYiğit et. al.…”
Section: Discussionmentioning
confidence: 99%